The Development of Sociocultural Malay-Based on Folklore Teaching Materials for Class X at SMA N 1 Percut Sei Tuan Deli Serdang - Junifran Junifran; Rosliani Rosliani (BIRCU, 2020)
This study aims to determine the results of the development of sociocultural-based folklore teaching materials in class X at SMA Negeri 1 Percut Sei Tuan. SMA Negeri 1 Percut Sei Tuan is a public school in the city of Medan and is located in Percut Sei Tuan Village. The teaching materials developed are modules. This research is a development research based on the development model from Borg and Gall. The subjects consisted of material experts, design experts, Indonesian language teachers, and class X students of SMA Negeri 1 Percut Sei Tuan. The results showed that (1) the sociocultural values contained in the folklore of Putri Hijau and Hikayat Si Khalib include, (a) religious values, (b) solidarity values, (c) the value of unity, (d) the value of struggle, and (e) cultural values. (2) Validation from material experts includes the feasibility of content getting 92.68% in the